Analisis Yuridis Konflik Penguasaan Tanah antara Masyarakat Adat dan Negara dalam Perspektif Hukum Agraria - Teguh Wicaksono (Jurnal Begawan Hukum (JBH), 2026)
Land tenure conflicts between indigenous peoples and the state remain a persistent issue in Indonesia. These conflicts arise due to differences between customary law practiced by indigenous communities and the formal legal system enforced by the state. This study aims to analyze the legal recognition of indigenous land rights within the national agrarian law framework, identify the causes of such conflicts, and formulate equitable solutions for their resolution. This research employs a normative legal method using statutory and conceptual approaches. The findings reveal that although legal recognition of indigenous land rights exists in various regulations, its implementation remains weak. Conflicts are primarily caused by overlapping regulations, economic interests, and the lack of formal recognition of customary territories. Therefore, regulatory harmonization, strengthening legal recognition of indigenous peoples, and the development of participatory and socially just dispute resolution mechanisms are essential. In conclusion, the protection of indigenous land rights can be optimized within the national agrarian legal framework through comprehensive legal reform and inclusive governance.